Strategic planning for information systems - a case study of a UK metropolitan council. - FLYNN, D.J. (1994)
Describes how the council's planning process started and the point to which it has evolved. Discusses the constraints found in adopting a textbook 'strategic' approach to planning for use within the essentially political process of strategy planning.